High-spin-state cobaltosic oxide anchored ruthenium monatomic composite catalyst as well as preparation method and application thereof
By synthesizing high-spin state tricobalt tetroxide-anchored ruthenium single-atom catalysts in situ on flexible carbon cloth, the problems of poor load controllability and high cost in the prior art are solved, and efficient dual-function catalytic performance of electrolytic water is achieved, which is suitable for large-scale industrial production.
Patent Information
- Application Number
- CN202510287946.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-07-01
AI Technical Summary
The existing single-atom catalyst synthesis methods have poor load controllability, high cost, and large energy consumption. The catalyst is not firmly bonded on the electrode surface and has poor contact, which affects the electrode catalytic activity and stability.
The pretreated flexible carbon cloth is used as the reaction template to synthesize a high-spin state tricobalt tetroxide-anchored ruthenium single-atom catalyst through hydrothermal reaction, and lattice distortion is achieved using hydrochloric acid etching to form a porous nanosheet structure, rich in high-spin Co3+, and serve as a dual-function catalyst for electrolytic water.
It improves the catalytically active adsorption site, reduces the amount of precious metals used, significantly reduces the overpotential of hydrogen evolution reaction and oxygen evolution reaction, and shows excellent bifunctional catalytic performance of electrolytic water, which is suitable for large-scale industrial production.
Smart Images

Figure CN120231092A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of composite catalysts in materials science, and particularly relates to a high-spin cobalt tetroxide anchored ruthenium single-atom composite catalyst, a preparation method thereof, and an application thereof. Background Art
[0002] Due to the limited reserves of fossil energy and the environmental pollution caused by combustion, the energy problem has become a major problem that needs to be solved urgently in human society. Electrochemical water splitting provides a sustainable strategy to provide clean energy through the cathodic hydrogen evolution reaction and the anodic oxygen evolution reaction. However, due to the slow kinetic rate of the reaction, a catalyst must be used to accelerate it. Since ruthenium has a lower cost, the hydrogen binding strength in the hydrogen evolution reaction is similar to that of platinum, and the activity in the oxygen evolution reaction is comparable to that of iridium, ruthenium has become a remarkable bifunctional catalyst and can replace platinum used in the hydrogen evolution reaction and iridium used in the oxygen evolution reaction. Especially when the size of the ruthenium catalyst is reduced to the single-atom scale, its unique structural characteristics can improve the metal utilization efficiency, thereby minimizing the consumption of ruthenium.
[0003] Cobalt tetroxide containing a redox pair is considered to be one of the most promising alternatives to noble metal oxide catalysts in alkaline media. However, in practical applications, the activity of cobalt tetroxide catalysts is poor. Researchers usually adopt a surface modification strategy to reduce the reaction overpotential by adjusting its surface structure and electronic properties, thereby improving the intrinsic activity of the catalyst. For example, designing and constructing electrocatalysts with special structures is beneficial to the exposure of more electrocatalytic active sites and the stability of the catalyst structure. Among them, ions in the high-spin state usually have more unpaired electrons, and the transition of unpaired electrons may affect the conductivity and the electron transfer process in the catalytic reaction. Researchers have found that high-spin Co 3+ In the oxygen evolution reaction (OER), the adsorption energy of intermediates can be optimized through a more flexible electron configuration, which can improve the electrocatalytic efficiency. In addition, as a strong OH* intermediate adsorption site, it can accelerate the hydrogen evolution reaction rate, promote the formation and coverage of oxygen-containing intermediates at the same time, and thus undergo a more kinetically favorable oxygen evolution reaction, showing excellent bifunctional catalytic performance for water electrolysis.
[0004] In recent years, single-atom catalysts reported as a hot research direction in the field of catalysis have attracted extensive attention. Compared with traditional nanoparticle catalysts, single-atom catalysts have many unique characteristics, such as high atomic utilization rate and maximum active sites, which can reduce the usage of metals and lower costs. In addition, single atoms also have unique coordination and electronic effects, making single-atom catalysts exhibit excellent catalytic performance in redox reactions, oxygen evolution reactions, hydrogen evolution reactions, etc.
[0005] However, the synthesis methods of single-atom anchored catalysts reported at the present stage have limitations, such as poor loading controllability, high cost, and high energy consumption. In addition, usually, the prepared electrocatalyst needs to be loaded on the substrate by methods such as physical vapor deposition and chemical adsorption. Poor binding, poor contact, and uneven dispersion of the catalyst on the electrode surface will all lead to blocked charge transfer, seriously affecting the catalytic activity and stability of the electrode. Summary of the Invention
[0006] To solve the above problems in the prior art, the present invention provides a composite catalyst of ruthenium single atoms anchored on high-spin cobalt tetroxide, a preparation method thereof, and an application thereof. Using pretreated flexible carbon cloth as a reaction template, a high-spin cobalt tetroxide anchored ruthenium single atom catalyst with a porous nanosheet structure is in-situ synthesized by hydrothermal reaction. The presence of high-spin Co 3+ can achieve a faster hydrogen evolution reaction (HER) rate, and at the same time, an oxygen evolution reaction (OER) that is more favorable kinetically occurs. Therefore, the composite catalyst can be used as a bifunctional catalyst for hydrogen evolution reaction and oxygen evolution reaction.
[0007] The first object of the present invention is to provide a preparation method of a composite catalyst of ruthenium single atoms anchored on high-spin cobalt tetroxide, including the following steps:
[0008] S1 Take a certain amount of cobalt chloride hexahydrate, ruthenium chloride, and sodium hydroxide in sequence and dissolve them in deionized water, and stir evenly to obtain a first mixed solution;
[0009] S2 Obtain pretreated flexible carbon cloth, and place the pretreated flexible carbon cloth and the first mixed solution into the inner liner of a hydrothermal reaction kettle in sequence for hydrothermal reaction to obtain a first composite;
[0010] S3 Take out the first composite from the hydrothermal reaction kettle, wash it with deionized water and ethanol, and then place it in a freeze dryer for drying to obtain a second composite;
[0011] S4 Anneal the second composite in an argon environment to obtain a third composite;
[0012] S5 Add the third composite to a hydrochloric acid solution for etching treatment, then rinse and dry it with deionized water to obtain a composite catalyst of ruthenium single atoms anchored on high-spin cobalt tetroxide nanosheets.
[0013] Specifically, in step S1, the content of cobalt chloride hexahydrate is 1.25 - 1.5 mmol, the content of ruthenium chloride is 0.25 - 0.3 mmol, and the content of sodium hydroxide is 0.1 - 0.2 mol; the volume of deionized water is 15 mL.
[0014] Specifically, the reaction temperature of the hydrothermal reaction described in step S2 is 130 °C, and the reaction time is 12 h;
[0015] Specifically, the specific method for obtaining the pretreated flexible carbon cloth described in step S2 includes: adding the second mixed solution into a hydrothermal reaction kettle, then soaking the flexible carbon cloth in the second mixed solution at a temperature of 30 °C for ultrasonic treatment for 15 min, and then placing the hydrothermal reaction kettle in a vacuum drying oven at a temperature of 60-80 °C for drying for 8-12 h to remove the residual second mixed solution, obtaining the dried flexible carbon cloth; then soaking the dried flexible carbon cloth in a sulfuric acid solution for 1 h, then washing it with deionized water until neutral, and then placing it in a vacuum drying oven at a temperature of 60 °C for drying for 12 h to obtain the pretreated flexible carbon cloth; wherein, the purity of the flexible carbon cloth is 95%, and the size is 3×2 cm 2 。
[0016] Specifically, the second mixed solution described in step S2 is composed of acetone and absolute ethanol mixed in a volume ratio of 1:1; the sulfuric acid solution is composed of deionized water and sulfuric acid mixed in a volume ratio of 1:(1-1.5).
[0017] Specifically, the treatment temperature of the annealing treatment is 400-600 °C, and the treatment time is 2-4 h.
[0018] Specifically, the concentration of the hydrochloric acid solution in step S5 is 1 mol / L, and the treatment time of the etching treatment is 18-24 h.
[0019] The second object of the present invention is to provide a high-spin state cobalt tetroxide anchored ruthenium single-atom composite catalyst prepared by the above method. The composite catalyst includes a substrate of pretreated flexible carbon cloth and an active substance with high-spin state cobalt tetroxide anchored ruthenium single atoms grown thereon; the composite catalyst has a high-spin porous nanosheet structure.
[0020] The third object of the present invention is to provide a composite catalyst as described above. The composite catalyst is rich in high-spin Co 3+ , and the high-spin state ions can accelerate the hydrogen evolution reaction rate and are also beneficial to the occurrence of the oxygen evolution reaction. It can be used as a catalyst for the hydrogen evolution reaction and the oxygen evolution reaction. The composite catalyst is used as a bifunctional catalyst in the hydrogen evolution reaction and the oxygen evolution reaction of electrolyzed water.
[0021] The fourth object of the present invention is to provide an application of the composite catalyst as described above as a bifunctional catalyst for electrolyzed water in an AEM anion electrolytic cell. The composite catalyst is placed in the AEM anion electrolytic cell as a bifunctional catalyst for electrolyzed water.
[0022] Compared with the prior art, the present invention has the following beneficial technical effects:
[0023] (1) The preparation method of the high-spin cobalt tetroxide anchored ruthenium single-atom composite catalyst provided by the present invention uses the pretreated flexible carbon cloth as a reaction template to in-situ synthesize a low-spin cobalt tetroxide anchored ruthenium single-atom composite structure. Subsequently, lattice distortion occurs through hydrochloric acid etching to achieve the transformation of cobalt elements from the low-spin state to the high-spin state, obtaining a ruthenium single-atom anchored high-spin cobalt tetroxide composite catalyst with a porous nanosheet structure, effectively increasing the active adsorption sites of the catalyst and enhancing the catalytic activity of the catalyst.
[0024] (2) The present invention performs a pretreatment operation on the flexible carbon cloth to activate its reactivity and improve its hydrophilicity. In addition, the addition of a small amount of ruthenium in the first mixed solution cannot generate strong interfacial charge transfer or lattice deformation, which is crucial for realizing the spin state regulation of (hydroxide). The preparation method provided by the present invention greatly improves the utilization rate of ruthenium single atoms, reduces the usage amount of precious metals, reduces production costs, and at the same time the synthesis process is easy to control;
[0025] (3) The composite catalyst prepared by the present invention is rich in high-spin Co 3+ As a strong OH* adsorption site, it can accelerate the hydrogen evolution reaction rate, and can also promote the formation and coverage of oxygen-containing intermediates, thereby occurring an oxygen evolution reaction that is more favorable kinetically. As a bifunctional catalyst for water electrolysis, it significantly reduces the overpotentials of the hydrogen evolution reaction and the oxygen evolution reaction, has good stability, and exhibits excellent bifunctional catalytic performance for water electrolysis;
[0026] (4) The present invention anchors ruthenium single atoms on the flexible carbon cloth with a porous nanosheet structure of high-spin cobalt tetroxide. Placed in an AEM anion exchange membrane electrolytic cell, it can make the electrolytic cell react efficiently at a lower applied voltage in an alkaline medium and has good stability; at the same time, for the anion exchange membrane electrolytic cell, it saves its energy consumption, improves efficiency, is suitable for large-scale industrial production, and has good application prospects. Description of the Drawings
[0027] Figure 1 Magnetic behavior curve of the composite catalyst a1 prepared in Example 1 of the present invention;
[0028] Figure 2 Scanning electron microscope image of the composite catalyst a1 prepared in Example 1 of the present invention at 200 nm;
[0029] Figure 3 Transmission electron microscope image of the composite catalyst a1 prepared in Example 1 of the present invention at 50 nm;
[0030] Figure 4 High-resolution transmission electron microscope image of the composite catalyst a1 prepared in Example 1 of the present invention at 1 nm;
[0031] Figure 5 X-ray diffraction pattern of the composite catalyst a1 prepared in Example 1 of the present invention;
[0032] Figure 6 Device diagram of the electrolytic water electrode a1 prepared in Example 1 of the present invention placed in an electrochemical three-electrode test system as an electrolytic water hydrogen evolution electrode;
[0033] Figure 7 Linear voltammetry scanning curve of the composite catalyst a1 prepared in Example 1 of the present invention placed in an electrochemical three-electrode test system for hydrogen evolution reaction and oxygen evolution reaction;
[0034] Figure 8 Performance stability curve of the composite catalyst a1 prepared in Example 1 of the present invention placed in an electrochemical three-electrode test system for hydrogen evolution reaction and oxygen evolution reaction;
[0035] Figure 9 Device diagram of the electrolytic cell with the composite catalyst a1 prepared in Example 1 of the present invention placed in an AEM anion exchange membrane electrolytic cell;
[0036] Figure 10 Membrane electrode assembly diagram of the composite catalyst a1 prepared in Example 1 of the present invention placed in an AEM anion exchange membrane electrolytic cell;
[0037] Figure 11 Electrolysis performance diagram of the composite catalyst a1 prepared in Example 1 of the present invention placed in an AEM anion exchange membrane electrolytic cell. Detailed implementation manners
[0038] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the content in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
[0039] Unless otherwise defined, all technical and scientific terms used in this specification have the same meaning as commonly understood by those skilled in the technical field to which the present invention belongs. The terms used in the specification of the present invention are only for the purpose of describing specific implementation manners and are not used to limit the present invention. The term "and / or" used in this specification includes any and all combinations of one or more of the related listed items. It should be understood that unless otherwise specified, various raw materials in the present invention can be obtained commercially.
[0040] Example 1
[0041] S1: 1.25 mmol of cobalt chloride hexahydrate, 0.25 mmol of ruthenium oxide and 0.1 mol of sodium hydroxide are dissolved in 15 mL of deionized water and stirred for 2 hours to obtain a first mixed solution a1;
[0042] S21 first obtains the pretreated flexible carbon cloth a1, and the specific steps include: mixing 30 mL of acetone and 30 mL of ethanol to obtain a second mixed solution a1, and then adding the second mixed solution a1 to a hydrothermal reactor to obtain a 95% purity and a size of 3×2 cm 2 The flexible carbon cloth is immersed in a second mixed solution at a temperature of 30°C and ultrasonically treated for 15 minutes, and then the hydrothermal reactor is placed in a vacuum drying oven at a temperature of 60°C and dried for 12 hours to remove the residual second mixed solution a1, thereby obtaining the dried flexible carbon cloth a1; the dried flexible carbon cloth a1 is immersed in a sulfuric acid solution for 1 hour, then washed with deionized water until neutral, and then placed in a vacuum drying oven at a temperature of 60°C and dried for 12 hours to obtain the pretreated flexible carbon cloth a1; wherein the sulfuric acid solution is a mixture of 100 mL of deionized water and 100 mL of sulfuric acid;
[0043] S22, the pretreated flexible carbon cloth a1 and the first mixed solution a1 are added to the polytetrafluoroethylene lining of the hydrothermal reactor, and the reactor is placed in an oven at 130° C. for hydrothermal reaction for 12 hours to obtain the first composite a1;
[0044] S3: taking out the first complex a1 from the hydrothermal reactor, washing it repeatedly with deionized water and ethanol for 5 times, and then placing it in a freeze dryer for drying until it is completely freeze-dried to obtain the second complex a1;
[0045] S4: placing the second composite a1 in an argon environment at 400° C. for annealing for 2 hours to obtain a third composite a1;
[0046] S5: adding the third complex a1 into a 1 mol / L hydrochloric acid solution for etching for 24 hours, then rinsing with deionized water and drying for multiple times to obtain a high-spin cobalt tetroxide nanosheet anchored ruthenium single atom composite catalyst a1.
[0047] Example 2
[0048] S1: 1.3 mmol of cobalt chloride hexahydrate, 0.3 mmol of ruthenium oxide and 0.15 mol of sodium hydroxide are dissolved in 15 mL of deionized water and stirred for 2 hours to obtain a first mixed solution a2;
[0049] S21 first obtains the pretreated flexible carbon cloth a2. The specific steps include: mixing 30 mL of acetone and 30 mL of ethanol evenly to obtain the second mixed solution a2, then adding the second mixed solution a2 into a hydrothermal reaction kettle, taking the flexible carbon cloth with a purity of 95% and a size of 3×2 cm 2 and soaking it in the second mixed solution a2 at a temperature of 30°C for ultrasonic treatment for 15 min, and then placing the hydrothermal reaction kettle in a vacuum drying oven at a temperature of 70°C for drying for 10 h to remove the residual second mixed solution a2, obtaining the dried flexible carbon cloth a2; then soaking the dried flexible carbon cloth a1 in a sulfuric acid solution for 1 h, then washing it with deionized water until neutral, and then placing it in a vacuum drying oven at a temperature of 60°C for drying for 12 h to obtain the pretreated flexible carbon cloth a2; wherein the sulfuric acid solution is composed of 100 mL of deionized water and 115 mL of sulfuric acid;
[0050] S22 Then add the pretreated flexible carbon cloth a2 and the first mixed solution a2 into the polytetrafluoroethylene inner liner of the hydrothermal reaction kettle, and place the reaction kettle in an oven at 130°C for hydrothermal reaction for 12 h to obtain the first composite a2;
[0051] S3 Take out the first composite a2 from the hydrothermal reaction kettle, wash it repeatedly with deionized water and ethanol for 5 times, and then place it in a freeze dryer for drying treatment until it is completely freeze-dried to obtain the second composite a2;
[0052] S4 Anneal the second composite a2 in an argon environment at 500°C for 3 h to obtain the third composite a2;
[0053] S5 Add the third composite a2 into a hydrochloric acid solution with a concentration of 1 mol / L for etching treatment for 22 h, and then rinse and dry it with deionized water for many times to obtain the high-spin state cobalt tetroxide nanosheet anchored ruthenium single-atom composite catalyst a2.
[0054] Example 3
[0055] S1 Take 1.5 mmol of cobalt chloride hexahydrate, 0.3 mmol of ruthenium oxide and 0.2 mol of sodium hydroxide and dissolve them in 15 mL of deionized water in sequence, and stir evenly for 2 h to obtain the first mixed solution a3;
[0056] S21 first obtains the pretreated flexible carbon cloth a3. The specific steps include: mixing 30 mL of acetone and 30 mL of ethanol evenly to obtain the second mixed solution a3, then adding the second mixed solution a3 into a hydrothermal reaction kettle, taking the flexible carbon cloth with a purity of 95% and a size of 3×2 cm 2The flexible carbon cloth is immersed in the second mixed solution a3 at a temperature of 30 °C and ultrasonically treated for 15 min. Then, the hydrothermal reaction kettle is placed in a vacuum drying oven at a temperature of 80 °C and dried for 8 h to remove the residual second mixed solution a3, obtaining the dried flexible carbon cloth a3. The dried flexible carbon cloth a3 is then immersed in the sulfuric acid solution for 1 h, followed by washing with deionized water until neutral, and then placed in a vacuum drying oven at a temperature of 60 °C and dried for 12 h to obtain the pretreated flexible carbon cloth a3. The sulfuric acid solution is composed of 100 mL of deionized water and 110 mL of sulfuric acid;
[0057] S22 Then, the pretreated flexible carbon cloth a3 and the first mixed solution a3 are added to the polytetrafluoroethylene inner liner of the hydrothermal reaction kettle, and the reaction kettle is placed in an oven at 130 °C for hydrothermal reaction for 12 h to obtain the first composite a3;
[0058] S3 The first composite a3 is taken out from the hydrothermal reaction kettle, washed repeatedly 5 times with deionized water and ethanol, and then placed in a freeze dryer for drying treatment until completely freeze-dried to obtain the second composite a3;
[0059] S4 The second composite a3 is placed in an argon atmosphere at 600 °C for annealing treatment for 4 h to obtain the third composite a3;
[0060] S5 The third composite a3 is added to a hydrochloric acid solution with a concentration of 1 mol / L for etching treatment for 18 h, and then rinsed and dried with deionized water for many times to obtain a composite catalyst a3 with high-spin cobalt tetroxide nanosheets anchored with ruthenium single atoms.
[0061] Test Example
[0062] Figure 1 This is the magnetic behavior curve graph of the composite catalyst a1 prepared in Example 1 of the present invention. The μ of p-Ru-Co3O4 calculated according to the Langevin theory eff is about 3.96 μ B , close to the theoretical value of Co3O4. Compared with the reference Co3O4, the μ of a-Ru-Co3O4 eff is larger, being 4.36 μ B , which proves that the spin state of the Co site has increased, generating high-spin Co 3+ . Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) are used to observe the microstructure of the material. Please refer to Figure 2 , Figure 3 and Figure 4 , Figure 2 This is the scanning electron micrograph of the composite catalyst a1 prepared in Example 1 of the present invention at 200 nm; Figure 3 This is the transmission electron micrograph of the composite catalyst a1 prepared in Example 1 of the present invention at 50 nm.Figure 4 This is the high-resolution transmission electron microscopy image of the composite catalyst a1 prepared in Example 1 of the present invention at 1 nm. From Figure 2 it can be seen that the composite catalyst a1 with a porous nanosheet structure was successfully loaded on the carbon cloth substrate. From Figure 3 it can be seen that the composite catalyst a1 has more mesopores, which is beneficial to accelerating mass transfer and exposing more active sites. From Figure 4 High-resolution transmission electron microscopy (HRTEM) characterization shows that the composite catalyst a1 prepared in Example 1 exhibits a regular nanosheet morphology, and there are obvious bright-field contrast differences in the catalyst lattice structure. The discrete sites with high brightness are confirmed to be Ru substances dispersed as single atoms through analysis. Since Ru atoms have a higher atomic number and a larger atomic radius compared to Co atoms, they will show a significant brightness difference during imaging. This characteristic phenomenon indicates that Ru atoms have successfully embedded into the Co3O4 lattice system through the atomic substitution mechanism, forming a stable single-atom catalyst structure. Figure 5 This is the X-ray diffraction pattern of the composite catalyst a1 prepared in Example 1 of the present invention. Compared with the reference sample Co3O4 (JCPDS 43-1003), the diffraction peaks of a1 and a2 have shifted by about 0.1° to lower diffraction angles, and no peaks related to Ru are found, indicating that Ru has been successfully doped into the lattice.
[0063] Application Example
[0064] The composite catalyst a1 prepared in Example 1 was used as a bifunctional catalyst in the hydrogen evolution reaction and oxygen evolution reaction of water electrolysis. The electrochemical performance test for use as a bifunctional reaction catalyst for water electrolysis was carried out according to the following method: (1) Electrochemical three-electrode test system: Please refer to Figure 6 , Figure 6 This is the device diagram of the electrolytic water electrode a1 prepared in Example 1 of the present invention placed in the electrochemical three-electrode test system as the hydrogen evolution electrode for water electrolysis; the composite catalyst with a size of 0.3 cm 2 was directly used as the working electrode. When testing the hydrogen evolution reaction, the counter electrode was a graphite electrode; when testing the oxygen evolution reaction, the counter electrode was a platinum sheet electrode, and the saturated calomel electrode was used as the reference electrode. The electrochemical test was carried out on a Chenhua (CHI 760E) electrochemical workstation. The electrolyte was 1 mol / L potassium hydroxide solution. Before the oxygen evolution reaction test, oxygen was introduced into the electrolyte for 30 min for saturation treatment and the oxygen atmosphere was maintained during the test;
[0065] (2) Linear sweep voltammetry curve test: The scanning speed was 5 mV / s, and it was converted into the electrode potential relative to the reversible hydrogen electrode. The calculation formula was: overpotential = electrode potential + 0.059 * pH + 0.2415 - 1.23 (V). Figure 7The linear voltammetry scanning curve graph of the composite catalyst a1 prepared in Example 1 of the present invention when hydrogen evolution reaction and oxygen evolution reaction occur in an electrochemical three-electrode test system; From Figure 7 It can be seen that in a 1M potassium hydroxide alkaline solution, for the hydrogen evolution reaction at the cathode to reach a current density of 10 mA cm -2 , only an ultra-low overpotential of 14 mV is required, and for the oxygen evolution reaction at the anode to reach a current density of 10 mA cm -2 , only an ultra-low overpotential of 256 mV is required, significantly reducing the energy consumption of the hydrogen evolution reaction and the oxygen evolution reaction.
[0066] (3) Stability test: Apply a current density of 10 mA / cm 2 on the same electrode and record the potential-time curve for 60 h. Figure 8 The performance stability curve graph of the composite catalyst a1 prepared in Example 1 of the present invention when hydrogen evolution reaction and oxygen evolution reaction occur in an electrochemical three-electrode test system; From Figure 8 It can be seen that the composite catalyst a1 prepared in Example 1 of the present invention has a stability of more than 60 h at a voltage of 10 mA / cm 2 , showing good stability and excellent bifunctional catalytic performance for water electrolysis.
[0067] Place the composite catalyst a1 prepared in Example 1 in an AEM anion electrolytic cell as a bifunctional catalyst for water electrolysis. Figure 9 The electrolytic cell device diagram of the composite catalyst a1 prepared in Example 1 of the present invention placed in an AEM anion exchange membrane electrolytic cell; Figure 10 The membrane electrode assembly diagram of the composite catalyst a1 prepared in Example 1 of the present invention placed in an AEM anion exchange membrane electrolytic cell; Figure 11 The electrolytic performance graph of the composite catalyst a1 prepared in Example 1 of the present invention placed in an AEM anion exchange membrane electrolytic cell; From Figure 11 it can be seen that at current densities of 100 and 500 mA cm -2 , the assembled AEM electrolytic cell only requires electrode voltages of 1.47 and 1.68 V respectively, significantly reducing the overpotential of the hydrogen evolution reaction and the oxygen evolution reaction. When the electrode voltage is 2.0 V, the electrolytic cell can reach a large current density of 1.46 A cm -2 , showing excellent catalytic performance and significantly reducing the energy consumption of the electrolytic cell.
Claims
1. A method for preparing a high-spin cobalt tetraoxide anchored ruthenium single atom composite catalyst, characterized in that A high performance bifunctional catalyst is obtained by a multi-step process, comprising the following steps: S1: taking a certain amount of cobalt chloride hexahydrate, ruthenium chloride and sodium hydroxide in turn and dissolving them in deionized water, and stirring them evenly to obtain a first mixed solution; S2: obtaining the pretreated flexible carbon cloth, and sequentially placing the pretreated flexible carbon cloth and the first mixed solution into the lining of a hydrothermal reactor for hydrothermal reaction to obtain a first composite; S3: taking out the first complex from the hydrothermal reactor, washing it with deionized water and ethanol, and then placing it in a freeze dryer for drying to obtain a second complex; S4: placing the second composite in an argon environment for annealing to obtain a third composite; S5 adds the third complex into a hydrochloric acid solution for etching, and then rinses and dries with deionized water to obtain a high-spin cobalt tetroxide nanosheet-anchored ruthenium single-atom composite catalyst.
2. The preparation method according to claim 1, characterized in that: In step S1, the content of cobalt chloride hexahydrate is 1.25-1.5 mmol, the content of ruthenium chloride is 0.25-0.3 mmol, the content of sodium hydroxide is 0.1-0.2 mol; and the volume of deionized water is 15 mL.
3. The preparation method according to claim 1, characterized in that: The reaction temperature of the hydrothermal reaction in step S2 is 130° C. and the reaction time is 12 h.
4. The preparation method according to claim 1, characterized in that: The specific method for obtaining the pretreated flexible carbon cloth in step S2 includes: adding the second mixed solution to the hydrothermal reactor, then immersing the flexible carbon cloth in the second mixed solution at a temperature of 30°C for ultrasonic treatment for 15 minutes, and then placing the hydrothermal reactor in a vacuum drying oven at a temperature of 60 to 80°C for drying for 8 to 12 hours to remove the residual second mixed solution to obtain the dried flexible carbon cloth; then immersing the dried flexible carbon cloth in a sulfuric acid solution for 1 hour, then washing it with deionized water until it is neutral, and then placing it in a vacuum drying oven at a temperature of 60°C for drying for 12 hours to obtain the pretreated flexible carbon cloth; wherein the purity of the flexible carbon cloth is 95%, and the size is 3×2 cm 2 .
5. The preparation method according to claim 4, characterized in that: In step S2, the second mixed solution is formed by mixing acetone and anhydrous ethanol in a volume ratio of 1:1; the sulfuric acid solution is formed by mixing deionized water and sulfuric acid in a volume ratio of 1:(1-1.5).
6. The preparation method according to claim 1, characterized in that: The annealing treatment in step S4 is performed at a temperature of 400 to 600° C. and for a time of 2 to 4 hours.
7. The preparation method according to claim 1, characterized in that: The concentration of the hydrochloric acid solution in step S5 is 1 mol / L, and the etching treatment time is 18 to 24 hours.
8. A high-spin cobalt tetraoxide anchored ruthenium single-atom composite catalyst prepared by any one of the methods of claims 1 to 7, characterized in that: The composite catalyst comprises a pretreated flexible carbon cloth substrate and an active substance on which high-spin cobalt tetraoxide anchoring ruthenium single atoms are grown; the composite catalyst has a porous nanosheet structure.
9. Use of the composite catalyst according to claim 8 as a bifunctional catalyst, characterized in that: The composite catalyst is rich in high-spin Co 3+ , can be used as a bifunctional catalyst in hydrogen evolution reaction and oxygen evolution reaction in water electrolysis.
10. Use of the composite catalyst according to claim 8 as a bifunctional catalyst in an AEM anion electrolyzer, characterized in that: The composite catalyst is placed in an AEM anion electrolyzer as a bifunctional catalyst for water electrolysis.